2020
DOI: 10.1088/1755-1315/485/1/012136
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of financial technology in increasing society’s financial inclusions in the industrial era 4.0

Abstract: Entering the current 4.0 industrial revolution occurred so rapidly technological developments in various sectors of life, including in the financial sector. Technological developments that occurred in the financial sector is slowly changing the financial industry into the digital age. There has been a shift of financial institutions that are now beginning to shift towards technology-based financial institutions. One of the advances in the current financial field adaptation Fintech (Financial Technology). The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…According to Mardiana et al (2020) studied a survey on the contribution of financial technology in increasing society's financial inclusions in the industrial era 4.0.The government targets financial inclusion to increase by 75% by 2019 and the survey shown that with the increasing number of fintech companies operating in Indonesia, they will increasingly reach communities in the main rural areas far from where financial services are available, because fintech can be accessed online very quickly and easily through each smartphone. Then this will certainly be able to help the achievement of government targets in increasing the financial inclusion of the Indonesian people.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…According to Mardiana et al (2020) studied a survey on the contribution of financial technology in increasing society's financial inclusions in the industrial era 4.0.The government targets financial inclusion to increase by 75% by 2019 and the survey shown that with the increasing number of fintech companies operating in Indonesia, they will increasingly reach communities in the main rural areas far from where financial services are available, because fintech can be accessed online very quickly and easily through each smartphone. Then this will certainly be able to help the achievement of government targets in increasing the financial inclusion of the Indonesian people.…”
Section: Empirical Reviewmentioning
confidence: 99%